Perceptions of harm from secondhand smoke exposure among U.S. adults, 2009–2010 - Kruger, Judy (Tob Induc Dis, 2016)
BACKGROUND: Exposure to secondhand smoke (SHS) causes significant disease and death. We assessed the prevalence and correlates of perceptions about the health harm of SHS among U.S. adults at the national and state level. METHODS: Data came from the 2009–2010 National Adult Tobacco Survey, a national landline and cellular telephone survey. Perceptions about the health harms of SHS were assessed as follows: ‘not at all harmful’, ‘somewhat harmful’, and ‘very harmful’. Descriptive statistics were used to assess the prevalence of SHS harm perceptions by tobacco use and sociodemographic factors, including sex, age, race/ethnicity, education, marital status, annual household income, region, sexual orientation, children in the household, and smoke-free law coverage. Logistic regression was used to assess odds of perceiving SHS to be “very harmful” (vs. “not at all harmful” or “somewhat harmful”), adjusting for the aforementioned factors. RESULTS: Nationally, 64.5 % of adults perceived SHS as ‘very harmful’ (state range: 73.5 % [Utah] to 53.7 % [Kentucky]). By tobacco use, the perception that SHS is ‘very harmful’ was: 76.5 % among nonusers of tobacco; 62.1 % among noncombustible only users; 47.9 % among combustible only users; and 40.8 % among dual combustible and noncombustible users. Following adjustment, the perception that SHS was ‘very harmful’ was higher among females, non-Hispanic minorities and Hispanics, respondents living with children, and states with 100 % smoke-free law coverage. Among current tobacco users the odds of perceiving SHS to be ‘very harmful’ was lower in the Midwest than the West. CONCLUSIONS: Almost two-thirds of American adults perceive SHS as ‘very harmful’; however, currently only half of all Americans are protected by comprehensive state or local smoke-free laws. These findings underscore the importance of public education campaigns to increase awareness of SHS exposure harm and the benefits of smoke-free environments. Expanding comprehensive smoke-free laws could protect all Americans from SHS.